ANALISIS PENGARUH EMISI CO2, LISTRIK TENAGA AIR, ENERGI TERBARUKAN, DAN KEDATANGAN WISATAWAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA 1992-2022 - Ningtyas, Nadya Asoka; Andriyani, Nur; Dewi Nuraini, Candra (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
This study aims to see the effect of CO2 emission, Hydropower, Renewable Energy and International Tourism Arrivals effect Economic Growth, which is interpered by GDP. Using a case study of Indonesia and annual data for 1992-2022, obtained from the World Bank and the Energy Institute. Type of this is quantitative reserarch by appling the Error Correction Model (ECM) method to examine how emission, hydropower, renewable energy and international tourism arrivals effect GDP in the short term and in the long term. The results showed a positive relatioship between CO2, HYP, RE, TA with GDP in the short and long term. While HYP in the short and long term, has a significant negative effect on GDP